Enabling Multi-Chemisorption Sites on Carbon Nanofibers Cathodes by an In-situ Exfoliation Strategy for High-Performance Zn–Ion Hybrid Capacitors - He, Hongcheng; Lian, Jichun; Chen, Changmiao; Xiong, Qiaotian; Li, Cheng Chao; Zhang, Ming (Nano-Micro Letters, 2022)
Carbon nanofibers films are typical flexible electrode in the field of energy storage, but their application in Zinc-ion hybrid capacitors (ZIHCs) is limited by the low energy density due to the lack of active adsorption sites. In this work, an in-situ exfoliation strategy is reported to modulate the chemisorption sites of carbon nanofibers by high pyridine/pyrrole nitrogen doping and carbonyl functionalization. The experimental results and theoretical calculations indicate that the highly electronegative pyridine/pyrrole nitrogen dopants can not only greatly reduce the binding energy between carbonyl group and Zn2+ by inducing charge delocalization of the carbonyl group, but also promote the adsorption of Zn2+ by bonding with the carbonyl group to form N–Zn–O bond. Benefit from the multiple highly active chemisorption sites generated by the synergy between carbonyl groups and pyridine/pyrrole nitrogen atoms, the resulting carbon nanofibers film cathode displays a high energy density, an ultralong-term lifespan, and excellent capacity reservation under commercial mass loading (14.45 mg cm‒2). Particularly, the cathodes can also operate stably in flexible or quasi-solid devices, indicating its application potential in flexible electronic products. This work established a universal method to solve the bottleneck problem of insufficient active adsorption sites of carbon-based ZIHCs.Imoproved should be changed into Improved. Highlights: 1 The high pyridine/pyrrole nitrogen-doped and carbonyl-functionalized nanosheets on flexible electrospun porous carbon nanofibers film cathode integrates the advantages of large specific surface area, strong hydrophilicity and high Zn2+ adsorption activity. 2 The Zinc-ion hybrid capacitors exhibits a high capacitance retention of 99.2% over 200,000 cycles at 40 A g−1. 3 A synergistic Zn2+ storage mechanism between carbonyl and pyridine/pyrrole nitrogen atoms is proposed.